(untitled) - Estaire, Sheila (Oxford, UK, 1994)
The book offers useful ideas and techniques for all the different steps in the planning stage, leading to the implementation and evaluation of the process. There is attention to the different teacher skills, such as negotiating, monitoring and motivating. Each section is supported by photocopiable checklists, grids and samples of units carried out by practising sedondary school teachers
Keywords: English language,Curriculum planning; Study and teaching,Foreign speakers